Efektivitas Progesteron Dalam Mengembalikan Siklus Menstruasi Pada Penderita Polycystic Ovary Syndrome (Pcos) Serta Tinjauannya Dalam Pandangan Islam - Dewi, Latifah Ratna; Maulina, Fita; Arsyad, M.; Sari, Siti Maulidya; Anshar, Muh. Fazlurrahman (Syntax Corporation, 2026)
Polycystic ovary syndrome (PCOS) can cause menstrual cycle disorders such as oligomenorrhea or amenorrhea, which can be treated with progesterone therapy. The choice of progesterone therapy depends on the patient's clinical condition, the effectiveness of the therapy, and potential side effects. This study aims to assess the effectiveness of progesterone in restoring menstrual cycles in PCOS sufferers. The research method was conducted through a survey using a Google Form distributed to members of the Indonesian PCOS Fighter community. Data included menstrual cycle changes, the type of progesterone used, dosage, duration of consumption, and factors influencing therapy effectiveness. Descriptive and bivariate analyses were used to assess the relationship between variables. The results showed that micronized progesterone was the most commonly used type, but the type of progesterone did not significantly affect therapy effectiveness. Most respondents required 4-6 months for menstrual cycle regularity, and progesterone dosage was not significantly associated with therapy effectiveness. Exercise and a high-protein, low-sugar diet were significantly associated with menstrual cycle regularity, while vitamin D consumption and a history of diabetes or obesity were not significantly associated. The study concluded that the effectiveness of progesterone therapy is more influenced by the patient's metabolic condition, endometrial response, and lifestyle quality. The use of progesterone hormone therapy is considered permissible in Islam as an effort to maintain women's health and fertility.